PTU-073 In Patients with IBD Switching from Originator Infliximab (Remicade) to Biosimilar Infliximab (CT-P13) Is Safe and Effective. (17th August 2016) - Rahmany, S; Cotton, S; Garnish, S; Brown, M; Saich, R; Lloyd, D; Gordon, JN
Abstract : Introduction: Biosimilar infliximab (CT-P13) has been licensed for the treatment of IBD in Europe for over a year with the potential for significant cost savings. However, uptake in the UK has been slow primarily due to concerns over the lack of safety and efficacy data particularly with regard to switching patients from the originator product. We present the preliminary data from a controlled switch programme in a cohort of adult IBD patients. Methods: A prospective study was undertaken to assess the safety and efficacy of switching patients receiving originator infliximab (Remicade) to its biosimilar (CT-P13). Patient demographic data was collected along with disease severity scores (HBI and SCCAI), biological markers of disease activity, drug and antibody levels and PROM data (IBD-Control questionnaire) prior to the switch and at each subsequent infusion visit. Evaluation of the efficacy of biosimilar infliximab at the time of the last infusion was compared with the originator at switch over. Means, medians, and ranges were calculated. Adverse events were prospectively collected. Results: 78 IBD patients were included in the cohort (63 CD and 15 UC). The average age for the CD and UC patients was 43 and 42 years respectively. The average length of therapy on Remicade prior to the switch was 46 months for CD and 25 months for UC. 66/78 (85%) patients were receiving the standard dosage of 5 mg/kg 8 weekly with 12/78 (15%) either on a shortened interval or a 10 mg/kg dose. 42/63 (67%) of CD patients were in remission at switch over compared to 43/60 (72%) at the most recent infusion (4–6 months). The number of patients with mild, moderate and severe disease remained stable throughout the study period (Mild 10/63 (16%) v 11/60 (18%): Moderate 10/63 (16%) v 5/60 (8%): Severe 1/63 (2%) v 1/60 (2%)). 9/15 (60%) of UC patients were in remission at switch over compared with 11/13 (85%) at the most recent infusion. There was no difference in the mean CRP before and after the switch in either CD patients (5.4 vs 5.6 p=0.32) or UC patients (3.1 vs 3.0 p=0.73). The mean patient questionnaire score data also remained unchanged before and after the switch (CD 4.4 vs 4.0 p=0.56, UC 4.9 vs 3.1 p=0.61). Five patients (3 CD, 2 UC) discontinued infliximab during the study period (3 switched biological class, 1 infusion reaction, 1 deep remission). There were no adverse safety signals with one infusion reaction (1/283 infusions) and the rate of mild adverse events unchanged from before and after the switch. Conclusion: Switching patients with IBD from originator infliximab to biosimilar infliximab appears both safe and effective. Wider uptake in the UK would result in considerable cost savings to the NHS. Disclosure of Interest: None Declared